2008
DOI: 10.1111/j.1365-2958.2008.06487.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of VceA and VceC, two members of the VjbR regulon that are translocated into macrophages by the Brucella type IV secretion system

Abstract: SummarySurvival and replication inside host cells by Brucella spp. requires a type IV secretion system (T4SS), encoded by the virB locus. However, the identity of the molecules secreted by the T4SS has remained elusive. We hypothesized that proteins translocated by the T4SS would be co-regulated with the virB operon. The LuxR family regulator VjbR, known to regulate virB, bound a fragment of the virB promoter containing an 18 bp palindromic motif (virB promoter box), showing that VjbR regulated the virB operon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
221
3
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(236 citation statements)
references
References 72 publications
9
221
3
3
Order By: Relevance
“…To date, 15 T4SS substrates have been identified (4 -8, 28), but we do not know the molecular mechanism that mediates their secretion and/or translocation. Interestingly, some of these effectors, like SepA, Bpe123, Bpe275, Bpe043, VceC, BspC, BspE, and BspB, either have a predicted periplasmic signal peptide or a transmembrane domain (5)(6)(7)(8), which highlights the complexity of the secretion process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, 15 T4SS substrates have been identified (4 -8, 28), but we do not know the molecular mechanism that mediates their secretion and/or translocation. Interestingly, some of these effectors, like SepA, Bpe123, Bpe275, Bpe043, VceC, BspC, BspE, and BspB, either have a predicted periplasmic signal peptide or a transmembrane domain (5)(6)(7)(8), which highlights the complexity of the secretion process.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that this new effector protein is secreted in a VirB-dependent manner, that its inactivation affects the intracellular trafficking particularly during the initial stages, and that its secretion involves a periplasmic intermediate (6). Although in Brucella this was the first report identifying a VirB substrate with a twostep secretion process involving a periplasmic intermediate, it was reported that other effectors have a predicted periplasmic signal peptide or putative transmembrane domains (5,7,8). We report here the identification in Brucella of a homologue of the A. tumefaciens virJ gene and characterized this gene genetically and biochemically.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Examples are (1) VceA and VceC, which belong to the VjbR regulon, consequently having their expression coregulated with the VirB T4SS (de Jong et al 2008); (2) BPE123, whose translocation additionally depends on a Sec-secretion signal at the amino terminus; and (3) BPE005, BPE275, and BPE043 (Table 1) (Marchesini et al 2011). Other putative effectors with indefinite positively charged amino acid carboxy-terminal sequences are (1) RicA, which is the sole effector having an assigned host partner, the guanosine di-phosphate (GDP)-bound form of the small GTPase Rab2 (de Barsy et al 2011); (2) Btp1 (TcpB in B. melitensis), which regulates innate immune responses via its Toll/interleukin-1 receptor (TIR) domain (Cirl et al 2008;Salcedo et al 2008) and possibly modulates microtubule dynamics (Radhakrishnan et al 2011); (3) PrpA, a proline-racemase family member, which regulates immune responses (Spera et al 2006); (4) CstA (conserved Sec24A-targeted protein A), which controls Brucella intracellular trafficking (de Barsy et al 2012); and (5) BvfA, which is required for Brucella intracellular replication (Lavigne et al 2005).…”
Section: Machineries Indispensable For Host Interactionsmentioning
confidence: 99%
“…Until now, little has been known about the nature and the molecular functions of Brucella effectors. Several proteins were identified as T4SS substrates, but their functions remain unknown (de Jong et al, 2008;Marchesini et al, 2011). Recently, the RicA Brucella effector involved in Rab2 recruitment on the BCVs was identified using a yeast two-hybrid (Y2H) screen (de Barsy et al, 2011).…”
Section: Introductionmentioning
confidence: 99%